The immunogenicity and safety of the new, Indonesian DTwP-HB-Hib vaccine compared to the DTwP/HB vaccine given with the Hib vaccine - Novilia Sjafri Bachtiar; Kusnandi Rusmil; Sunarjati Sudigdoadi; Cissy B Kartasasmita; Hadyana Hadyana (Paediatrica Indonesiana, 2017)
Background Haemophilus influenzae type b (Hib) causes infection with predominant manifestations of pneumonia, meningitis, and other invasive diseases, occurring primarily in children aged under 2 years, particularly in infants.Â  The World Health Organization (WHO) and Indonesian Technical Advisory Group for Immunization recommend to include the Hib vaccine into the national immunization program. The newly developed DTwP-HB-Hib combination vaccine is anticipated to be the preferred choice for Hib vaccine introduction; it is efficient, simple, and has higher coverage.Objective To evaluate the immunogenicity and safety of a new, combined Bio Farma DTwP-HB-Hib vaccine, compared to the registered Hib monovalent vaccine given simultaneously with the local DTwP-HB vaccine, when used as the primary vaccination of Indonesian infants.Methods A prospective, randomized, open-label, phase II study was conducted on the DTwP-HB-Hib vaccine compared to the Hib (registered) vaccine given simultaneously with the DTwP-HB vaccine, in Bandung from July 2011 to January 2012. Infants were serially vaccinated at 6-11, 10-15, and 14-19 weeks. Serological assessments were done prior to the first vaccine dose and 28 days after the third dose. Safety was assessed from the time of first injection until 1 month after the last injection.Results Of 220 healthy infants enrolled, 211 completed the study, with 105 receiving the combined vaccine and 106 the two separate vaccines. All vaccines were well tolerated. No differences in rates of local and systemic reactions were seen between the two methods of administration. No serious adverse events were considered to be related to the vaccines. In the DTwP-HB-Hib primary-vaccination group, at least 98% of the infants reached protective levels of antibodies (seropositivity) against the antigens employed in the vaccines while 96% in the control group.Conclusion The DTwP-HB-Hib combined vaccine is immunogenic and safe, as well as comparable to the Hib vaccine given simultaneously with to the DTwP-HB vaccine.